The acquisition of science process skills through entrepreneurial physics education in senior secondary schools - Akinbobola, Akinyemi Olufunminiyi; Bada, Abiodun Adekunle (REID (Research and Evaluation in Education), 2022)
The need for the acquisition of science process skills is gaining acceptance in secondary school as a crucial preparatory skill for promoting entrepreneurship. The problem of unemployment is a challenge facing many developing nations, with no exception to the developed nations. In the current study, the effect of the acquisition of science process skills through entrepreneurship education on 125 Nigerian senior secondary school students' achievement and retention in "Physics in Technology" was investigated. The study adopts the randomized pre-test-post-test control group quasi-experimental design. A group of students was taught using science process skills through the entrepreneurship method, while the other group was taught using the conventional lecture method. A researcher-made instrument, Achievement Test in Physics (ATP), was used to collect data for the study. Overall, this investigation reports that students who acquired science process skills through the entrepreneurship method achieved and retained significantly better than those students taught with the conventional method. The results indicate that science process skills acquisition and entrepreneurship education are indispensable towards self-reliance and sustainable development of the nation. Also, students taught science process skills using the entrepreneurship method retained what had been learned better than the other group, and the method did not segregate along student gender. This paper contributes to scholastic by making a case for incorporating entrepreneurship education into the senior secondary school Physics curriculum. This would assist in the production of secondary school students whose creativity, ingenuity, and resourcefulness can assist in reducing the problem of unemployment through the encouragement of entrepreneurship.